1994
DOI: 10.1002/hed.2880160403
|View full text |Cite
|
Sign up to set email alerts
|

Complications of craniofacial resection for tumors involving the anterior skull base

Abstract: Future endeavors for prevention of complications should focus on antibiotic prophylaxis and reconstruction of the cranial base defect with better vascularized flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
3
13

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 19 publications
8
145
3
13
Order By: Relevance
“…Ao associar-se a este procedimento de grande porte, uma reconstrução complexa e de tempo prolongado como a microcirúrgica, poderia se esperar um aumento significativo desta morbidade. Entretanto, a reparação com retalhos livres reduz a morbidade cirúrgica das ressecções craniofaciais 6,[12][13][14] . A taxa de complicação de 58,6% é semelhante às encontradas na literatura, que variam de 16 a 64% 8,10,13,15 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Ao associar-se a este procedimento de grande porte, uma reconstrução complexa e de tempo prolongado como a microcirúrgica, poderia se esperar um aumento significativo desta morbidade. Entretanto, a reparação com retalhos livres reduz a morbidade cirúrgica das ressecções craniofaciais 6,[12][13][14] . A taxa de complicação de 58,6% é semelhante às encontradas na literatura, que variam de 16 a 64% 8,10,13,15 .…”
Section: Discussionunclassified
“…Entretanto, a reparação com retalhos livres reduz a morbidade cirúrgica das ressecções craniofaciais 6,[12][13][14] . A taxa de complicação de 58,6% é semelhante às encontradas na literatura, que variam de 16 a 64% 8,10,13,15 . As infecções locais ocorreram em 21,7% dos casos, sendo a complicação mais comum, talvez justificada pela inclusão em nossa avaliação de complicações locais como deiscências e infecções restritas, ou ao freqüente estado geral seriamente comprometido destes pacientes , seja pela gravidade da doença ou pelo baixo nível sócio-econômico e negligência nos cuidados com a saúde.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A review of the literature demonstrates postcraniotomy rates of intracranial air ranging from 1% to 16%. 24,27,40,41 Some authors have reported a 100% incidence of pneumocephalus if imaging is done within the first 2 days of supratentorial craniotomy. 50 Clearly, the timing and resolution of the imaging technique will alter pneumocephalus rates as air is progressively absorbed after surgery.…”
Section: Postoperative Pneumocephalusmentioning
confidence: 99%